Setting the parameters of the burnout rate of samples of flame-retardant cellulose-containing materials - Tsapko, Yu.; Bondarenko, O.; Tsapko, O.; Apanasenko, V.; Kaverin, K.; Zherebchuk, D. (Ways to Improve Construction Efficiency, 2023)
The paper deals with the issues of fire protection of cellulose-containing materials, in particular sailcloth and wood. The combustion process of materials is influenced by their physical properties: density, thermal conductivity, heat capacity, as well as a number of other factors, such as humidity, the ratio between the reacting surface and the volume or mass of the material that is ignited, its position in the heat flow, air flow velocity or draft, and the degree of heat concentration during combustion. The description of the behavior of fire retardants and coatings, including swelling coatings, at the time of formation of the insulating structure is a separate and complex task. In general, it covers both stages of the thermal protection process: as a rule, the decomposition of flame retardants under the influence of temperature with heat absorption and the release of non-combustible gases, and subsequently the swelling of the coating formed during fire protection. Therefore, there is a need to study the conditions for the formation of a barrier to thermal conductivity and to establish the mechanism of fire protection from layer to layer of coke. In this regard, a study of the fire protection process during the operation of the fireproof coating was carried out. As a result of the research, it was found that the burnout rate of fire-retardant cellulose-containing materials depends on four parameters, namely, the parameter characterizing the intensity of flame combustion development (α, s-1), the intensity of suppression of combustion reactions due to fire protection of materials (γ, s-1), the intensity of material combustion at the initial moment of time (ω0, kg/(m2·s2)), and the initial burnout rate (u0, kg/(m2·s)). The dependence of the extreme moment of time was obtained, in which the mass burnout rate of a sample of fire-protected material is minimal (the burnout rate of wood samples treated with fire-protective agents (compared to untreated ones) decreases by 3.6 times), which makes it possible to more effectively determine the effect of impregnating compositions on the burning of samples of cellulose-containing materials.